Adobe Photoshop Cs6 Bible
The Photoshop CS6 Bible is the only book you need to succeed in any Photoshop endeavor. It shows readers how to retouch, color correct, manipulate, and combine images using Photoshop CS6. Readers will learn to create cutting-edge special effects for their digital or film-based images, and use them on the Web or in print. The easy and approachable writing style demystifies even the most complex Photoshop tasks. You\\\'ll master every aspect of Photoshop from image-editing basics to techniques for working with camera raw images. Other topics covered include the File Browser, histogram palette, Lens Blur, Match Color, the color replacement tool, customizable keyboard shortcuts, as well as covering all the new features and enhancements made in the latest version of Photoshop CS6.